EUROPEAN UNION IN FUNCTION OF DEVELOPMENT AND PROMOTION OF SMALL AND MEDIUM ENTERPRISES (EU and comparative law issues and challenges series (ECLIC), 2018)
Small and medium enterprises are a vital force for economy development. Activities on EU level are necessary in order for unique commodity market to remain open and fair. Modern entrepreneurship has a dominant significance in economy and often referred as entrepreneurship economy or entrepreneurship society. In EU, around 99 % of the enterprises are designed as small and medium enterprises. SME represents 98 % enterprises and 67 % of working places and crucial force for economic growth, innovations, employability and social integrations in EU. Hence, European Commission promotes successful entrepreneurship and enhances the business environment for SME. SME in Europe represents a sociological phenomenon since SME provides solutions to so many existential questions, economic growth and development, business competitiveness and development of working places. This paper is concerned with the current situation of SME in Europe and examines the possibilities of SME for further development as a crucial economic force in EU, strategic EU needs as well as the politics for promotion of SME. The paper present current statistical data.